2019
DOI: 10.1002/ejp.1483
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of functional outcome in musculoskeletal healthcare: An umbrella review

Abstract: Background Multiple cohort and systematic review studies exist, reporting independent predictive factors associated with outcome in musculoskeletal populations. These studies have found evidence for a number of “generic” factors that have been shown to predict outcome across musculoskeletal patient cohorts. This review provides a higher level review of the evidence with a focus on generic patient factors associated with functional musculoskeletal outcome with a view to informing predictive modelling. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 43 publications
6
17
1
1
Order By: Relevance
“…A similar finding was recently described by Burgess et al. (2020), underlining age and BMI as strong predictors for functional outcome in musculoskeletal disorders, including OA and TKA. Furthermore, observations by Gay et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A similar finding was recently described by Burgess et al. (2020), underlining age and BMI as strong predictors for functional outcome in musculoskeletal disorders, including OA and TKA. Furthermore, observations by Gay et al.…”
Section: Discussionsupporting
confidence: 89%
“…age, BMI and gender, explained more variation than the self-reported functions, clinical pain or quantitative sensory profiling. A similar finding was recently described by Burgess et al (2020), underlining age and BMI as strong predictors for functional outcome in musculoskeletal disorders, including OA and TKA. Furthermore, observations by Gay et al (2019) found that the level of physical activity was associated with gender and BMI but not with pain in knee OA patients.…”
Section: Associationssupporting
confidence: 88%
“…In line with previous research, we found higher baseline disability and symptoms to be associated with greater improvement, whereas higher pain catastrophizing, lower educational level and unemployment/sick leave/working a subsidised job was associated with less improvement [ 8 , 62 ]. As previous literature, we found limited predictive value of sex [ 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…As the patients have undergone longer care trajectories prior to the municipal rehabilitation (general practitioner – secondary care – municipal rehabilitation), they typically present with persistent symptoms and complications. Further unsuccessful treatment increases the likelihood of persistent symptoms and reduces the effectiveness of future interventions [ 8 ]. This can lead to both higher tangible and intangible costs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that patients pain history and outcome expectations are strongly associated with prognosis for several musculoskeletal conditions (Burgess, Mansell, Bishop, Lewis, & Hill, 2020;Mallen et al, 2007;Mondloch et al, 2001;Myhrvold et al, 2019). In studies of musculoskeletal conditions, pain history is assessed traditionally as pain duration and/or number of previous episodes (Mallen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%